Linezolid for therapy of Staphylococcus aureus meningitis: a cohort study of 26 patients. Issue 11 (1st November 2020) - Pintado, Vicente; Pazos, Rosario; Jiménez-Mejías, Manuel Enrique; Rodríguez-Guardado, Azucena; Díaz-Pollán, Beatriz; Cabellos, Carmen; García-Lechuz, Juan Manuel; Lora-Tamayo, Jaime; Domingo, Pere; Muñez, Elena; Domingo, Diego; González-Romo, Fernando; et al.
Abstract: Background: Linezolid has good penetration to the meninges and could be an alternative for treatment of Staphylococcus aureus meningitis. We assessed the efficacy and safety of linezolid therapy for this infection. Methods: Retrospective multicenter cohort study of 26 adults treated with linezolid, derived from a cohort of 350 cases of S. aureus meningitis diagnosed at 11 university hospitals in Spain (1981-2015). Results: There were 15 males (58%) and mean age was 47.3 years. Meningitis was postoperative in 21 (81%) patients. The infection was nosocomial in 23 (88%) cases, and caused by methicillin-resistant S. aureus in 15 cases and methicillin-susceptible S. aureus in 11. Linezolid was given as empirical therapy in 10 cases, as directed therapy in 10, and due to failure of vancomycin in 6. Monotherapy was given to 16 (62%) patients. Median duration of linezolid therapy was 17 days (IQR 12-22 days) with a daily dose of 1, 200 mg in all cases. The clinical response rate to linezolid was 69% (18/26) and microbiological response was observed in 14 of 15 cases evaluated (93%). Overall 30-day mortality was 23% and was directly associated with infection in most cases. When compared with the patients of the cohort, no significant difference in mortality was observed between patients receiving linezolid or vancomycin for therapy of methicillin-resistant S. aureus meningitis (9% vs. 20%; p = .16) nor between patients receiving linezolid or cloxacillin for therapy of methicillin-susceptible S. aureus meningitis (20% vs 14%; p = .68). Adverse events appeared in 14% (3/22) of patients, but linezolid was discontinued in only one patient. Conclusions: Linezolid appears to be effective and safe for therapy of S. aureus meningitis. Our findings showed that linezolid may be considered an adequate alternative to other antimicrobials in meningitis caused by S. aureus.